Clinical Utility of Mindfulness Training in the Treatment of Fatigue After Stroke, Traumatic Brain Injury and Multiple Sclerosis: A Systematic Literature Review and Meta-analysis - Ulrichsen, Kristine M.; Kaufmann, Tobias; Dørum, Erlend S.; Kolskår, Knut K.; Richard, Geneviève; Alnæs, Dag; Arneberg, Tone J.; Westlye, Lars T.; Nordvik, Jan E. (Frontiers in Psychology, 2016)
Background: Fatigue is a common symptom following neurological illnesses and injuries, and is rated as one of the most debilitating sequela in conditions such as stroke, traumatic brain injury and multiple sclerosis. Yet effective treatments are lacking, suggesting a pressing need for a better understanding of its etiology and mechanisms that may alleviate the symptoms. Recently mindfulness-based interventions have demonstrated promising results for fatigue symptom relief. Objective: Investigate the efficacy of mindfulness-based interventions for fatigue across neurological conditions and acquired brain injuries. Materials and methods: Systematic literature searches were conducted in PubMed, Medline, Web Of Science and PsycINFO. We included randomized controlled trials applying mindfulness-based interventions in patients with neurological conditions or acquired brain injuries. Four studies (N = 257) were retained for meta-analysis. The studies included patients diagnosed with multiple sclerosis, traumatic brain injury and stroke. Results: The estimated effect size for the total sample was -0.37 (95% CI -0.58, -0.17). Conclusions: The results indicate that mindfulness- based interventions may relieve fatigue in neurological conditions such as stroke, TBI and MS. However, the effect size is moderate, and further research is needed in order to determine the effect and improve our understanding of how mindfulness-based interventions affect fatigue symptom perception in patients with neurological conditions.